KONTROL PENERANGAN TENAGA SURYA SEBAGAI IMPLEMENTASI DARI LISTRIK KERAKYATAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Solar Street Lighting Light (PJU-TS) is a street lighting that uses sunlight as a source of electrical energy. The Solar Street Lighting (PJU-TS) is suitable for roads in areas not covered by PLN electricity and also areas experiencing electrical energy crisis especially in remote areas. But recently PJU Solar is also rife applied in urban areas such as in the main streets, residential street, garden lights, campus area, factory area, bus stops, parking lots, gas stations (gas stations) and so on. In the process of making solar lighting control system on the lamp for PJU is first to determine the load installed, then calculate the number of solar panels or photovoltaic needs, then calculate the battery requirements and determine the capacity of the battery charge regulator (BCR). Then for PJU lamps to operate automatically installed light sensor or light dependent resistor (LDR) as a switch to turn on and off PJU lights.